Mol2all-videogame for the stoichiometry learning: identification of the charateristics game and player’s profile (2021)
For a large part of high school students learning stoichiometry is complex because they have deficiencies in mathematical logic and handling of proportions. This situation demotivates the student during their learning process, which exacerbates the problem of understanding this topic. This study proposes an investigation that will result in the implementation of a serious video game which motivates the learning of stoichiometric calculations. The scope of this article is the presentation of the study carried out to determine the profiles of the students in the role of players, and the characteristics of the video game that will be called Mol2All should have. In order to achieve it, this study used quantitative research, with a synthetic approach and a quasi-experimental design. It concluded that the profile of the student as a player is in accordance with Richard Bartle’s methodology, in addition, the study shows that the population that will benefit from the video game is wide, regardless of their socioeconomic status, their area of residence, gender or whether the educational institution is public or private. It was also determined that is important to use lightweight technologies adaptable to all types of electronic devices to be used in the construction of Mol2All.